Living in Lisbon - Sequeira, Marta (2023)
Lisbon is being ravaged by an unprecedented housing crisis. The exponential increase of prices, the combined outcome of the financialisation of housing and the lack of continued investment of public policies, means that every Portuguese person is, or knows someone who is, affected by the crisis. There is a restless public debate, but little has been told about the buildings that will give shape to the political strategies that are being conceived and implemented. Which city do we wish to build to face the problem? What can be the role of architecture in this context? Living in Lisbon concisely presents the conjecture and possibilities of action to think about the building of the city. The book includes an overview of the most charismatic architectures resulting from public housing policies that have been built in Lisbon over the course of 50 years of democracy, describes the main projects that are currently on the table, presents analytical visions of the present situation and freely envisions plans for the future in the form of dialogue, essay or manifesto.